HIP HOP: O ENSINO DAS RUAS - Rebello, Rudimar da Rocha Lyra (2018)
This dissertation entitled Hip Hop: Street teaching fostered actions with activists of the Guarapuava Hip Hop movement to promote community empowerment actions within and from the reality of the participants. For the theoretical methodological support, we used: Culture and Identity (MELUCCI, 2001; GEERTZ, 1989), Anthropology (GOLDMAN, 2006 NECKEL, 2017, OLIVEIRA 2013, SOUZA 2009 and FELIX 2004) Ethnography (TOSTA, 2005) and Learning Community GABASSA, 2009), among others. Four moments of action were developed together with members of the Hip Hop Movement: the first time there were meetings open to the Hip Hop militants, who served to make the local Hip Hop militants able to make use of the spaces of the State University of the Central-West UNICENTRO and at the same time explain about their participation in the Hip Hop of Guarapuava. The second moment was composed of itinerant events that provided the presentation of the four elements of Hip Hop to an audience beyond the participants of the research, also at that time it was possible to present more about the Hip Hop Culture trying to deconstruct prejudices regarding this culture both in the park center of the city and in the peripheral districts. In the third moment was held the First Week of Hip Hop Culture at UNICENTRO, that counted with shows of RAP, Graffiti, Breakdance and workshops given by members of the local Hip Hop. This event was the first that occurred in the University in this proportion, because it brought the prior knowledge of this urban culture, allowing the occupation of this space by the local Hip Hop militants, and it also allowed the academic community to know more about this movement. The fourth and final moment included the participation of Hip Hop activists in the Fifth Week of Integration Education, Research and Extension-SIEPE of UNICENTRO, this event had a Working Group on Urban Culture and Human Rights as well as RAP show in the auditorium Francisco Contini. At the end of this study it was observed that the initiatives of the Hip Hop movement can be configured within the definition of possessions, but this movement in Guarapuava acts in a fragmented way and its resistance to this occurs in several factors that occur in the course of this work. The activities of the militants conform to the characteristics of the learning community, since they can contribute to the construction of identity and actions in a community focused on political awareness and empowerment.